A Tale of Dynamical Instabilities and Giant Impacts in the Exoplanet Radius Valley - Sho Shibata; Andre Izidoro (The Astrophysical Journal Letters)
The size distribution of planets with radii between 1 R _⊕ and 4 R _⊕ peaks near 1.4 R _⊕ and 2.2 R _⊕ , with a dip around 1.8 R _⊕ —the so-called “radius valley.” Recent statistical analyses suggest that planets within this valley (1.5 <  R  < 2 R _⊕ ) tend to have slightly higher orbital eccentricities than those outside it. The origin of this dynamical signature remains unclear. We revisit the “breaking the chains” formation model and propose that late dynamical instabilities—occurring after disk dispersal—may account for the elevated eccentricities observed in the radius valley. Our simulations show that subvalley planets ( R  < 2 R _⊕ ) are generally rocky, while those beyond the valley ( R  > 2 R _⊕ ) are typically water-rich. Rocky planets that undergo strong dynamical instabilities and numerous late giant impacts have their orbits excited and their radii increased, ultimately placing them into the radius valley. In contrast, the larger, water-rich planets just beyond the valley experience weaker instabilities and fewer impacts, resulting in lower eccentricities. This contrast leads to a peak in the eccentricity distribution within the valley. The extent to which planets in the radius valley are dynamically excited depends sensitively on the orbital architecture before the orbital instability. Elevated eccentricities among radius valley planets arise primarily in scenarios that form a sufficiently large number of rocky planets within 100 days (typically ≳5) prior to instability, and that also host external perturbers ( P  > 100 days), which further amplify the strength of dynamical instabilities.